The height of female Brazilian beach volleyball players in relation to specialization and court dimensions - Medeiros, A.; Giatsis, G.; Palao, J. M.; Afonso, J.; Lopes, R.; Mesquita, I. (World Congress of Performance Analysis of Sport IX, 2012)
Rules changes made by the FIVB (Fédération Internationale de Volleyball) in 2001 (reduction of the court and new score system) have increased the duration of point rallies (Giatisis et al., 2003, 2005) and of game actions such as the attack (Giatsis et al., 2003). Analyzing FIVB World Tour players, Giatsis et al. found that after the changes the blockers and the defenders were significantly larger. The purpose of this paper was to analyze the effect of these rules changes in the height of Brazilian women beach volleyball players in relation to specialization. The sample included the winners of Brazilian CBV (Brazilian Volleyball Confederation) in seasons 1991 to 2011; Tournaments in 9x9m court, n=20 players; Tournaments in 8x8m court, n=21 players). The winners were categorized in relation to court dimensions (9x9m court and 8x8m court) and to their specialization: defenders (DE), blockers (BL) and without any specialization (NS). Data was collected in 2011 from the official site of the Brazilian Volleyball Confederation (www.cbv.com.br). One-way Anova and Post-hoc Dunnett C tests were performed to find differences in the winners` height in relation to their specialization and the court dimensions. The Post Hoc tests indicated significant differences (F (5.48) = 118. 43, p<0.001) between the DE9x9, DE8x8, BL9x9, BL8x8, NS9x9 and NS8x8 (see Table 1). These results show that, after reduction of the court dimensions (9x9 m to 8x8 m), the height of the defenders (M=1.68; M=1.71) and blockers (M=1.77; M=1.78) has increased significantly, while players without any specialization (M=1.77; M=1.73) significantly decreased. The results found support those found by Giatsis et al., (2011).